2005
DOI: 10.1128/iai.73.3.1820-1827.2005
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and Inflammation Deficiencies in Mongolian Gerbils Infected byHelicobacter pyloriChemotaxis Mutants

Abstract: Helicobacter pylori causes disease in the human stomach and in mouse and gerbil stomach models. Previous results have shown that motility is critical for H. pylori to colonize mice, gerbils, and other animal models. The role of chemotaxis, however, in colonization and disease is less well understood. Two genes in the H. pylori chemotaxis pathway, cheY and tlpB, which encode the chemotaxis response regulator and a methyl-accepting chemoreceptor, respectively, were disrupted. The cheY mutation was complemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(134 citation statements)
references
References 43 publications
6
124
1
3
Order By: Relevance
“…Multiple studies of Tlp proteins from the closely related organism H. pylori have demonstrated the functions of these proteins to be complex and not readily apparent when analyzed under in vitro conditions. Thus, several H. pylori tlp mutants have shown contradictory or host-dependent results in terms of colonization potential (3,12,32,39,49). However, the general picture from H. pylori, as well as C. jejuni, is that the Tlp proteins contribute to the physiological fitness of these organisms when facing the challenges encountered during host colonization.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies of Tlp proteins from the closely related organism H. pylori have demonstrated the functions of these proteins to be complex and not readily apparent when analyzed under in vitro conditions. Thus, several H. pylori tlp mutants have shown contradictory or host-dependent results in terms of colonization potential (3,12,32,39,49). However, the general picture from H. pylori, as well as C. jejuni, is that the Tlp proteins contribute to the physiological fitness of these organisms when facing the challenges encountered during host colonization.…”
Section: Resultsmentioning
confidence: 99%
“…We thus sought a different type of analysis to help characterize the chemotactic response to zinc and nickel. The Brucella broth soft agar migration assay has worked well for H. pylori (Beier et al, 1997;McGee et al, 2005), and so we embarked on adapting this assay to monitor specific chemoeffectors. In the standard version of this assay, bacteria migrate outwards from an inoculation point in response to gradients created either by consuming nutrients or producing waste products.…”
Section: H Pylori Temporal Swimming Assays Work Optimally With Fbs Amentioning
confidence: 99%
“…Che − mutants have early mouse colonization defects but achieve normal bacterial levels by 1 mo after inoculation (5,16). All cheY mutant-associated phenotypes can be complemented, indicating that loss of cheY is responsible for the chemotaxis and animalcolonization deficits (5,15). Using standard inflammation grading that captures the number and distribution of lymphocytes, we found that inflammation was significantly lower in mice infected for 2 mo with Che − H. pylori than in mice infected with wild-type H. pylori but was greater than in the no-H. pylori control (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…For these experiments, we orally infected mice with either wild-type H. pylori or an isogenic Che − mutant lacking a central chemotaxis protein, CheY. H. pylori cheY mutants have been characterized extensively and found to retain flagella and motility but to lack chemotaxis completely (5,15). Che − mutants have early mouse colonization defects but achieve normal bacterial levels by 1 mo after inoculation (5,16).…”
Section: Resultsmentioning
confidence: 99%